DIETARY CHITOSAN AND NANO-CHITOSAN OF BLACK SOLDIER FLY LARVAE FOR IMPROVING GROWTH AND PHYSIOLOGICAL INDICES OF Clarias gariepinus - Mardianto, Nawwar; Aryani, Retno; Rudianto, Rudianto; Manurung, Hetty; Nugroho, Rudy Agung (Jurnal Riset Akuakultur, 2025)
This research examined the effect of nutritional supplementation of 5% chitosan and nano-chitosan sourced from black soldier fly larvae exuviae on the growth and physiological profile of Clarias gariepinus (initial weight: 2.054 ± 0.02 g) over a period of 30 days. The feed treatments consisted of chitosan-supplemented, nano-chitosan-supplemented, and control feed, arranged in triplicate. In each trial unit, 30 fish were reared in plastic tanks (60 L capacity, filled with 50 L of freshwater). Growth, hematological profiles, and antioxidant activities were assessed after 30 days. The findings indicated that nano-chitosan markedly improved growth performance, as shown by increased final weight, body weight gain (BWG), and feed efficiency (FE), in comparison to chitosan and control diets. Specifically, nano-chitosan-fed fish exhibited a final weight of 2.878 ± 0.16 g ind-1 and a feed conversion ratio (FCR) of 1.376 ± 0.15, outperforming the chitosan group (2.660 ± 0.12 g ind-1; 1.267 ± 0.12) and the control group (2.344 ± 0.04 g ind-1; 1.857 ± 0.05). Additionally, nano-chitosan significantly increased activities of antioxidant enzymes, including those of superoxide dismutase (SOD) and catalase (CAT), while reducing malondialdehyde (MDA) levels, indicating reduced oxidative stress. The hematologicalprofile remained stable across the groups, confirming the safety of these feed additives. This research emphasizes nano-chitosan as a viable sustainable food additive for improving growth rate and oxidative resistance in C. gariepinus.  Penelitian ini mengevaluasi pengaruh suplementasi diet dengan 5% kitosan dan nano-kitosan dari cangkang pupa lalat tentara hitam terhadap pertumbuhan serta indeks fisiologis Clarias gariepinus (berat awal: 2,054 ± 0,02 g) selama 30 hari. Perlakuan pakan terdiri atas pakan yang disuplementasi nano-kitosan, disuplementasi kitosan, dan kontrol yang diulang tiga kali. Pada masing-masing unit percobaan, 30 ekor ikan dipelihara di wadah plastik (kapasitas 60 L, diisi dengan air sebanyak 50 L). Setelah 30 hari pemeliharaan, pertumbuhan, profil hematologi, dan aktivitas antioksidan dievaluasi. Hasil penelitian menunjukkan bahwa nano-kitosan meningkatkan kinerja pertumbuhan, yang ditunjukkan dengan peningkatan berat akhir, pertambahan bobot tubuh (PBT), dan efisiensi pakan (EP), dibanding dengan pakan kitosan dan kontrol. Secara khusus, ikan yang diberi pakan nano-kitosan menunjukkan bobot akhir 2,878 ± 0,16 g ekor-1 dan rasio konversi pakan (RKP) 1,376 ± 0,15, lebih tinggi dari kelompok kitosan (2,660 ± 0,12 g ekor-1; 1,267 ± 0,12) dan kelompok kontrol (2,344 ± 0,04 g ekor-1; 1,857 ± 0,05). Selain itu, nano-kitosan secara signifikan meningkatkan aktivitas enzim antioksidan, termasuk superoksida dismutase (SOD) dan katalase (CAT), sekaligus menurunkan kadar malondialdehida (MDA), yang mengindikasikan berkurangnya stres oksidatif. Parameter hematologi tetap stabil di seluruh kelompok, yang menegaskan keamanan bahan tambahan pakan ini. Penelitian ini menyoroti nano-kitosan sebagai suplemen pakan berkelanjutan yang menjanjikan untuk meningkatkan laju pertumbuhan dan ketahanan oksidatif pada C. gariepinus.